The Arabidopsis SIAMESE-RELATED Cyclin-Dependent Kinase Inhibitors SMR5 and SMR7 Regulate the DNA Damage Checkpoint in Response to Reactive Oxygen Species. Issue 1 (7th January 2014) - Yi, Dalong; Alvim Kamei, Claire Lessa; Cools, Toon; Vanderauwera, Sandy; Takahashi, Naoki; Okushima, Yoko; Eekhout, Thomas; Yoshiyama, Kaoru Okamoto; Larkin, John; Van den Daele, Hilde; Conklin, Phillip; Britt, Anne; et al.
Abstract : Reactive oxygen species (ROS) cause DNA damage. In this work, two SIAMESE/SIAMESE-RELATED ( SIM/SMR ) genes that encode cyclin-dependent kinase inhibitors are described as being part of a signaling pathway that arrests cell proliferation in response to ROS, revealing a novel cell cycle checkpoint-signaling cascade. Abstract: Whereas our knowledge about the diverse pathways aiding DNA repair upon genome damage is steadily increasing, little is known about the molecular players that adjust the plant cell cycle in response to DNA stress. By a meta-analysis of DNA stress microarray data sets, three family members of the SIAMESE/SIAMESE-RELATED ( SIM/SMR ) class of cyclin-dependent kinase inhibitors were discovered that react strongly to genotoxicity. Transcriptional reporter constructs corroborated specific and strong activation of the three SIM/SMR genes in the meristems upon DNA stress, whereas overexpression analysis confirmed their cell cycle inhibitory potential. In agreement with being checkpoint regulators, SMR5 and SMR7 knockout plants displayed an impaired checkpoint in leaf cells upon treatment with the replication inhibitory drug hydroxyurea (HU ). Surprisingly, HU -induced SMR5/SMR7 expression depends on ATAXIA TELANGIECTASIA MUTATED (ATM) and SUPPRESSOR OF GAMMA RESPONSE1, rather than on the anticipated replication stress-activated ATM AND RAD3-RELATED kinase. This apparent discrepancy was explained by demonstrating that, in addition to its effect on replication, HU triggers the formation of reactive oxygen species (ROS ). ROS -dependent transcriptional activation of the SMR genes was confirmed by different ROS -inducing conditions, including high-light treatment. We conclude that the identified SMR genes are part of a signaling cascade that induces a cell cycle checkpoint in response to ROS -induced DNA damage.